Synthesis and Crystal Structure of 2,3,4-Tri-O-acetyl-b-D-xylopyranosyl Isothiocyanate - Yang, Bo; Zhang, Shu-Sheng; Li, Ji-Zhi; Li, Xu-Mei; Jiao, Kui (Asian Journal of Chemistry, 2016)
The crystal structure of 2,3,4-tri-O-acetyl-b-D-xylopyranosyl isothiocyanate, C12H15NO7S, has been synthesized and its structure is determined by X-ray crystallography and TG/DTG method. The crystal belongs to triclinic system, space group PI with unit cell constants a = 7.824(3), b = 9.252(3), c = 10.827(4) Å3, Z = 1, Dc = 1.371 g/cm3, μ = 0.241 mm–1, R and wR are 0.0474 and 0.1171 respectively for 3548 unique reflections with 3018 observed reflections [I > 2s(I)]. All the ring substituents are in plane and occupy equatorial positions.